Malayan spymaster memoirs of a rubber planter, bandit fighter, and spy - Hembry, Boris (Monsoon, 2013)
A true story of 1930s Malaysia, of jungle operations, submarines and spies in WWII, and of the postwar Malayan Emergency, as experienced by an extraordinary man. Rubber planter Boris Hembry was a part of Freddy Spencer Chapman's covert Stay Behind Party in Japanese-occupied Malaya, a member of the Secret Intelligence Service, and he formed the first Home Guard unit in Malaya during the Emergency.